Advancement in the utilization of biomass-derived heterogeneous catalysts in biodiesel production - Mohammed, Nurudeen Ishola; Kabbashi, Nassereldeen Ahmed; Olanrewaju Alade, Abass; Sulaiman, Sarina (Scientic Research Publishing Inc., 2018)
Solid oxide catalysts derived from various renewable sources have produced significant yield of methyl esters of enhanced purity. These materials are sourced for due to their advantages ranging from low cost, recoverability and reusability, environmental benign-ness, thermal stability and high quality product generation. For a possible greener production process, many researchers in literature reported the use of biomass-derived heterogeneous catalyst in biodiesel synthesis producing high quality pure product. The catalysts were majorly modified through simple physical cost effective and energy saving operations. This paper explores some of these bio-based heterogeneous catalyst used in biodiesel production via transesterification and esterification approach and their performance in FAME yield and conversion. The feedstock consideration which warrant the route selection, various approaches that are adopted in biodiesel production, performance of renewable heterogeneous catalyst and the measures that were adopted to enhance efficiency of the catalyst were considerably highlighted. It is observed that the prospects of organic-based solid catalyst in biodiesel development is a promising enterprise compared to the conventional methods utilizing homogeneous chemical catalyst, which generates wastewater requiring treatment before disposal and generates product that may cause engine malfunction. This review work aimed at providing detailed and up-to-date record of the trend in renewable catalyst development in biodiesel synthesis. This is expected to inform a suitable selection and reaction conditions in the development of biodiesel from the very many feed stocks.